Selective Pharmacological Inhibition of the Pacemaker Channel Isoforms (HCN1-4) as New Possible Therapeutical Targets - Koncz, I.; Szel, T.; Jaeger, K.; Baczko, I.; Cerbai, E.; N. Romanelli, M.; Gy. Papp, J.; Varro, A. (Current Medicinal Chemistry, 2011)
The pacemaker channel isoforms are encoded by the hyperpolarization-activated and cyclic nucleotide-gated (HCN) gene family and are responsible for diverse cellular functions including regulation of spontaneous activity in sino-atrial node cells and control of excitability in different types of neurons. Four channel isoforms exist (HCN1-HCN4). The hyperpolarization-activated cardiac pacemaker current (If) has an important role in the generation of the diastolic depolarization in the sino-atrial node, while its neuronal equivalent (Ih) is an important contributor to determination of resting membrane potential, and plays an important role in neuronal functions such as synaptic transmission, motor learning and generation of thalamic rhythms. Ivabradine is a novel, heart rate-lowering drug which inhibits the pacemaker (If) current in the heart with high selectivity and with minimal effect on haemodynamic parameters. Ivabradine is beneficial in patients with chronic stable angina pectoris equally to beta receptor blocker and calcium channel antagonist drugs. There is increasing interest to apply this drug in other fields of cardiology such as heart failure, myocardial infarction, cardiac arrhyhtmias. Heart rate reduction might improve clinical outcomes in heart failure. HCN upregulation presumably contributes to increased (If) and may play a role in ventricular and atrial arrhythmogenesis in heart failure. In the nervous system the HCN channels received attention in the research areas of neuropathic pain, epilepsy and understanding the mechanism of action of volatile anaesthetics. This article delineates that the pharmacological modulation of cardiac and neuronal HCN channels can serve current or future drug therapy and introduces some recently investigated HCN channel inhibitor compounds being potential candidates for development.
Keywords: myocardial ischaemia